FABRICATION AND CHARACTERISATION OF XANTHAN GUM- GELATINE BLEND NANOFIBERS/PARTICLES PRODUCED BY ELECTROSPINNING METHOD - Dogan, Ecem; Sengor, Mustaf; Gunduz, Oguzha; Ustundag, Cem Bulent (SERBAN SOLACOLU FOUNDATION, 2023)
This study aims to obtain nanoparticles by electrospinning method using xanthan gum (XG) and gelatine (GEL) polymers. For the development of these nanoparticles, ten different groups were produced. In some groups, nanofiber was obtained instead of particles. The nanofiber formation was determined in the 10 wt% GEL, 12 wt% GEL, 3 wt% XG, 8 wt% GEL + 3 wt% XG. 12 wt% GEL + 0.1 wt% XG groups. 4 wt% GEL + 1 wt% XG and 8 wt% GEL + 3 wt% XG groups showed nanoparticles structure. To assess the nanofibers chemical properties, Fourier transform infrared spectroscopy (FTIR) were used. Scanning electron microscopy (SEM) was used to characterize mechanical and morphological properties. Physical properties and swelling behaviours were examined to analyse the samples. As a result of the swelling test, 3 wt% XG was degraded, 10 wt% and 12 wt% gelatin groups started to degrade after the fourth day. Our work deduced that GEL/XG nanoparticles could use for carrier purposes. Also, this study was beneficial in finding the right ratios in the production of nanoparticles and nanofibers from the XG/GEL mixture by electrospinning. In addition, proper electrospinning parameters in nanofiber and nanoparticles production are also important results of the study and will be further used in developing composite nanostructures with regenerative or drug release capability.
Keywords: gelatin; xanthan gum; electrospinning; particle; fiber; NANOFIBROUS SCAFFOLDS; POLYCAPROLACTONE; CHITOSAN; FIBERS; Construction & Building Technology; Materials Science